Memori serah terima jabatan Bupati Kepala Daerah Tingkat II Jepara, pada tanggal 5 Mei 1976 (Sekretariat Wilayah/Daerah Tingkat II Jepara, 1976)
Progress report of the development of Jepara Regency, Central Java; submitted on the occasion of the transfer of office from the old to the new regent, 1976.